Implementasi Pengabdian Masyarakat Melalui Pelatihan Pemecahan Soal High-Stake Test Kimia bagi Siswa SMAN 3 Siak Hulu - Oktariani Oktariani; Nurul Fauziah; Adinda Fathia (Jurnal Pengabdian UNDIKMA, 2023)
This service activity aims to increase knowledge and ability to solve high-stakes test questions as preparation for UTBK and KSN students of SMAN 3 Siak Hulu. Implementing this service used training with the evaluation instrument, namely a questionnaire, and was analyzed descriptively and quantitatively. The results of this dedication showed that students' knowledge and abilities had increased in solving high-stakes test questions in chemistry subjects. In addition, this activity could change students' paradigm towards learning chemistry, which was considered difficult to be easier, and could increase students' motivation to study chemistry. This service activity could also increase students' self-confidence and readiness to participate in KSN and UTBK.